Fish Community Structure The Dry Season in The Cipeles River, Sumedang Regency, West Java Province, Indonesia - Ayi Yustiati; Rostika Rostika; Ibnu Bangkit Bioshina Suryadi; Titin Herawati (Department of Biology, Faculty of Science and Technology, Syarif Hidayatullah State Islami, 2023)
AbstractCipeles River is a sub-watershed of the Cimanuk River that flows in Sumedang Regency, Indonesia. The upstream is located in Sukasari District and flows into Tomo District. This study aimed to determine the fish community structure in the Cipeles River during the dry season. This research was conducted from September to December 2020 using field observation methods and purposive sampling techniques at three stations (Station 1 at 6°48′59.5″S and 108°01′22.5″E; Station 2 at 6°48′56.2″S and 108°01′32.3″E; and Station 3 at 6°47′3.7″S and 108°05′44″E) data analysis employed descriptive-comparative. Parameters observed are abundance, diversity, dominance, uniformity, community structure, and water quality. The results showed that from 566 caught fish the diversity index is low with a value of 0.86–0.89, a moderate dominance index with a value of 0.55–0.62, and a low uniformity index of 0.16–0.17. Based on the three index values, it can be concluded that the fish community structure the dry season in the Cipeles River is categorized as depressed, caused by the high influence of total suspended solids that have exceeded the water quality threshold value for fisheries (according to regulation of the Government of the Republic of Indonesia Number 22 of 2021 on Spatial Management) with concentrations ranging from 67 mgL-1 to 74 mgL-1.AbstrakSungai Cipeles merupakan sub DAS dari Sungai Cimanuk yang mengalir di Kabupaten Sumedang, Indonesia. Hulunya terletak di Kecamatan Sukasari dan mengalir ke Kecamatan Tomo, Kabupaten Sumedang. Penelitian ini bertujuan untuk mengetahui struktur komunitas ikan di Sungai Cipeles pada musim kemarau. Penelitian dilakukan pada bulan September hingga Desember 2020 dengan menggunakan metode pengamatan lapangan dan teknik purposive sampling pada tiga stasiun (Stasiun 1 di 6°48′59.5″LS dan 108°01′22.5″BT, Stasiun 2 di 6°48′56.2″ S dan 108°01′32.3″BT, dan Stasiun 3 di 6°47′3.7″LS dan 108°05′44″E). Analisis data menggunakan deskriptif-komparatif. Parameter yang diamati adalah kelimpahan, keragaman, dominasi, keseragaman, struktur komunitas, dan kualitas air. Hasil penelitian menunjukkan bahwa dari 566 ikan yang ditangkap indeks keragamannya rendah dengan nilai 0,86–0,89, indeks dominansi sedang dengan nilai 0,55–0,62, dan indeks keseragaman rendah 0,16–0,17. Berdasarkan ketiga nilai indeks tersebut dapat disimpulkan bahwa struktur komunitas ikan pada musim kemarau di Sungai Cipeles dikategorikan tertekan, disebabkan oleh tingginya pengaruh total padatan tersuspensi yang telah melebihi nilai ambang batas kualitas air untuk perikanan (menurut Peraturan Pemerintah Republik Indonesia Nomor 22 Tahun 2021 tentang Penataan Ruang) dengan konsentrasi berkisar antara 67 mgL-1 sampai dengan 74 mgL-1.